2015
DOI: 10.1007/s10840-015-0054-9
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive focus localization, right ventricular epicardial potential mapping in patients with an MRI-conditional pacemaker system ‐ a pilot study

Abstract: BackgroundWith the advent of magnetic resonance imaging (MRI) conditional pacemaker systems, the possibility of performing MRI in pacemaker patients has been introduced. Besides for the detailed evaluation of atrial and ventricular volumes and function, MRI can be used in combination with body surface potential mapping (BSPM) in a non-invasive inverse potential mapping (IPM) strategy. In non-invasive IPM, epicardial potentials are reconstructed from recorded body surface potentials (BSP). In order to investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 26 publications
(22 reference statements)
0
2
0
Order By: Relevance
“…56 Despite these results, there has been some evidence that patients with high-risk cytogenetics like 17p deletion do benefit with a tandem transplant. 54,57 Transplant as salvage therapy Second ASCT is a safe and effective therapy in eligible patients with relapsed MM. Alvares and colleagues found that patients with a PFS of <18 m after first ASCT had a median OS of <6 m whereas those with a PFS of ⩾18 m showed a median OS approaching 3 years.…”
Section: Single Versus Tandem Transplantmentioning
confidence: 99%
See 1 more Smart Citation
“…56 Despite these results, there has been some evidence that patients with high-risk cytogenetics like 17p deletion do benefit with a tandem transplant. 54,57 Transplant as salvage therapy Second ASCT is a safe and effective therapy in eligible patients with relapsed MM. Alvares and colleagues found that patients with a PFS of <18 m after first ASCT had a median OS of <6 m whereas those with a PFS of ⩾18 m showed a median OS approaching 3 years.…”
Section: Single Versus Tandem Transplantmentioning
confidence: 99%
“…56 Despite these results, there has been some evidence that patients with high-risk cytogenetics like 17p deletion do benefit with a tandem transplant. 54,57…”
Section: Single Versus Tandem Transplantmentioning
confidence: 99%